Serviceability analysis of training aircraft subject to maintenance operations in a flight training organisation: a case study. (14th May 2021) - Aydin, Emre; Isilak, Cemal; Suzer, Ahmet Esat; Atasoy, Vehbi Emrah
The main aim of this study is to draw a framework for analysing the serviceability status of the available aircraft for flight operations. The monthly serviceability condition of each training aircraft, consisting of TB-20, Cessna 172 SP, and C90 aircraft, in the FTO fleet over a period of two years are investigated in detail. According to the results of the paper, the serviceability conditions of TB-20, Cessna 172 SP, and C90 are observed to be 73.27%, 73.4%, and 75.75%, respectively. It is concluded that the primary reasons for the unserviceability status of the aircraft are identified to be various maintenance activities including propeller governor, flap track slot, parking brake, vibration problem in the engine. This work sets a framework for the organisations that continue to work in the world or for new organisations to be opened.